Developing a survey tool to measure psychosocial risk and work performance at a workplace - Mohd Ishanuddin, Nuruzzakiyah; Abdul Aziz, Hanida; Sukadarin, Ezrin Hani (2023)
This paper aims to develop a survey tool for psychosocial risk and work performance in the manufacturing industry in Malaysia. A cross-sectional study was conducted among 258 respondents from the manufacturing plant. The validity and reliability of a set questionnaire adapted from the Copenhagen Psychosocial Questionnaire (COPSOQ III), NIOSH Generic Job Stress Questionnaire and Individual Work Performance Questionnaire (IWPQ 1.0) instruments were tested using Exploratory Factor Analysis (EFA) and reliability analysis. The results showed that the originated ten construct measures of psychosocial risk factors and work performance were reduced into eight construct measures understudy after conducting factor analysis by Principal Component Analysis as a dimensional reduction method. This current study is essential to explore the presence of psychosocial risk factors that underlying in the manufacturing industry which might affect worker performance and well-being. Also, for future research purposes, this study can be utilised as the main tool to explore the psychosocial risk factors and work performance in other sectors